2004
DOI: 10.1089/thy.2004.14.772
|View full text |Cite
|
Sign up to set email alerts
|

Primary Thyroid Lymphoma Associated with Graves' Disease

Abstract: We report herein a case of thyroid mucosa-associated lymphoid tissue (MALT) lymphoma in a patient receiving antithyroid drug therapy for Graves' disease. A 75-year-old woman first presented with finger tremor and was diagnosed with Graves' disease on the basis of clinical and laboratory findings. Three years later, she presented with rapid and painless enlargement of the thyroid. Ultrasonography revealed a circumscribed hypoechoic area bilaterally in each lobe of the thyroid, and fine-needle aspiration biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to some authors, Hashimoto thyroiditis is considered the most important risk factor for PTL appearance and a moderate risk factor for the papillary thyroid carcinoma [ 2 , 3 ]. The connection between Graves´ disease and PTL has also been described [ 15 ]. It seems that chronic antigenic stimulation of lymphocytes might have a role in DLBCL growth, while chronic inflammation can induce synthesis of cyclooxigenase-2, present in both, Hashimoto thyroiditis and thyroid carcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, Hashimoto thyroiditis is considered the most important risk factor for PTL appearance and a moderate risk factor for the papillary thyroid carcinoma [ 2 , 3 ]. The connection between Graves´ disease and PTL has also been described [ 15 ]. It seems that chronic antigenic stimulation of lymphocytes might have a role in DLBCL growth, while chronic inflammation can induce synthesis of cyclooxigenase-2, present in both, Hashimoto thyroiditis and thyroid carcinoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yamashita et al have also reported vitamin D deficiency in 40% of women and in 18% of men having GD from Japan [25]. In another study from Japan, Doi et al showed that 35% of patients with thyrotoxicosis had vitamin D deficiency [26]. Other studies have also shown a significant impact of 25OHD3 deficiency on bone structure and bone metabolism [27][28][29].…”
Section: Introductionmentioning
confidence: 95%